First isolation and molecular characterization of Toxoplasma gondii from a human placenta in Argentina - Pardini, Lais Luján (2014)
Blood sample and placenta were taken from a 37-week pregnant woman; serologic results indicated acute toxoplasmosis. Placenta was inoculated into mice. Seropositive mice were sacrificed and tissue cysts from brain were inoculated into new mice. Specific DNA was detected by PCR, and the isolate was characterized as Type II by nPCR-RFLP for nSAG2, SAG3, BTUB, GRA6, c29-2, c22-8, L358, PK1 and Apico markers. This is the first isolation and molecular characterization of Toxoplasma gondii from humans in Argentina.